Food Pedagogy and Parenting Programs In Improving Food Literacy of Early Childhood: A Systematic Literature Review - Jennita Maria Sembiring; Erie Siti Syarah; Siti Roudhotul Jannah (Journal of Islamic Education Students (JIES), 2026)
The increasing exposure of children to ultra-processed foods highlights the importance of developing food literacy from early childhood. This study aims to identify food pedagogy strategies applied in early childhood education, examine parenting-based nutrition programs influencing children’s food literacy, evaluate their effectiveness based on Scopus-indexed empirical studies, and identify research gaps in integrated school–family intervention models. This research employed a Systematic Literature Review guided by the PRISMA 2020 framework. Literature searches were conducted in Scopus and Web of Science for articles published between 2014 and 2025. After screening and eligibility assessment, twelve empirical studies were included in the analysis. The findings indicate that experiential food pedagogy approaches such as cooking activities, gardening, and project-based learning effectively enhance children’s food knowledge, skills, and attitudes toward healthy eating. Parenting-based nutrition programs also contribute significantly to improving children’s dietary behaviors through parental modeling and family engagement. However, most interventions are implemented separately within school or family contexts, indicating the need for integrated school–family intervention models to strengthen sustainable food literacy development in early childhood.